2005
DOI: 10.1158/1078-0432.ccr-04-2653
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Human Tumor Xenografts with Monoclonal Antibody 806 in Combination with a Prototypical Epidermal Growth Factor Receptor–Specific Antibody Generates Enhanced Antitumor Activity

Abstract: Monoclonal antibody (mAb) 806 is a novel epidermal growth factor receptor (EGFR) antibody with significant antitumor activity that recognizes a mutant EGFR commonly expressed in glioma known as delta2-7 EGFR (de2-7 EGFR or EGFRvIII) and a subset of the wild-type (wt) EGFR found in cells that overexpress the receptor. We have used two human xenograft mouse models to examine the efficacy of mAb 806 in combination with mAb 528, a prototypical anti-EGFR antibody with similar specificity to cetuximab. Treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 46 publications
5
79
0
Order By: Relevance
“…At least three independent groups, (Johns et al, 2003;Huang et al, 2004;Matar et al, 2004;Perera et al, 2005). In further support of this approach we have observed promising clinical activity of the combination of an EGFR TKI and cetuximab, a monoclonal antibody directed at the extracellular domain of the EGFR .…”
Section: Lapatinib-induced Stabilization and Accumulation Of Her2mentioning
confidence: 64%
“…At least three independent groups, (Johns et al, 2003;Huang et al, 2004;Matar et al, 2004;Perera et al, 2005). In further support of this approach we have observed promising clinical activity of the combination of an EGFR TKI and cetuximab, a monoclonal antibody directed at the extracellular domain of the EGFR .…”
Section: Lapatinib-induced Stabilization and Accumulation Of Her2mentioning
confidence: 64%
“…Sym004 led to rapid internalization and degradation of EGFR in cetuximab-resistant H226 clones with subsequent loss of proliferative effects (20). In line with these data, Pedersen et al reported that Sym004 synergistically inhibited skin, lung and HNSCC cell growth through efficient target internalization and degradation (34 528) showed synergistic anti-tumor activity in glioma and squamous cell cancer xenograft models (37).…”
Section: Discussionmentioning
confidence: 88%
“…Intracranial xenografts expressing the de2-7 EGFR have also been shown to be inhibited by mAb 806, and this observation represents the only reported mAb that has such effects on gliomas in vivo (30). In conjunction with other EGFR inhibitors such as the mAb 528, or the tyrosine kinase inhibitor AG1478, mAb 806 shows synergistic effects on xenograft growth, with Ͼ60% of established tumours showing complete regressions (29,31).…”
mentioning
confidence: 99%